2020
DOI: 10.1007/s10488-020-01022-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fidelity Outcomes of Paraprofessional and Professional Delivery of a Perinatal Depression Preventive Intervention

Abstract: Mothers and Babies (MB), a perinatal depression preventive intervention, has proven effective in decreasing depressive symptoms and preventing onset of major depression. An ongoing cluster-randomized trial is comparing the effectiveness of the six-session MB group intervention led by paraprofessionals versus mental health professionals. Twenty percent of all audio-recorded intervention sessions were randomly selected for fidelity checks. Analyses assessed mean facilitator adherence and competency overall, by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…Our findings suggest that provider education had little impact on training engagement and outcomes. They are consistent with those of other studies finding small or no associations between provider education and EBT delivery‐related outcomes, 38‐41,64,65 as well as studies finding advantages for providers without advanced degrees 42,45 . This study extends earlier work by using equivalence testing to answer this question in a large sample of providers delivering services to children and families.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings suggest that provider education had little impact on training engagement and outcomes. They are consistent with those of other studies finding small or no associations between provider education and EBT delivery‐related outcomes, 38‐41,64,65 as well as studies finding advantages for providers without advanced degrees 42,45 . This study extends earlier work by using equivalence testing to answer this question in a large sample of providers delivering services to children and families.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, we found that providers with and without advanced de- finding small or no associations between provider education and EBT delivery-related outcomes, [38][39][40][41]64,65 as well as studies finding advantages for providers without advanced degrees. 42,45 This study extends earlier work by using equivalence testing to answer this question in a large sample of providers delivering services to children and families. Our exploratory analyses of family clinical outcomes were largely inconclusive.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Though findings from LMICs are promising on LHWdelivered EBPs, minimal research has investigated if there are differences in clinical outcomes depending on provider experience and education level (Barnett, Gonzalez, et al, 2018). One recent study found similar levels of fidelity and effectiveness between LHW and professional delivery of a perinatal depression preventive intervention (Diebold et al, 2020;Tandon et al, 2021), but few other studies have made these comparisons. If LHWs are less effective at delivering EBPs than mental health professionals or their roles in auxiliary care diminishes effectiveness, disparities could be exacerbated for marginalized populations.…”
Section: Effectiveness: Are Lhw Models Of Care Effective?mentioning
confidence: 99%